Breast cancer clear & simple : all your questions answered (Clear & simple, 2016)
"A breast cancer resource for the newly diagnosed from the experts at the American Cancer Society With an easy-to-understand, question-and-answer format, this book guides patients through the important decisions they'll need to make, from diagnosis through treatment. It helps women with breast cancer and their caregivers know what to expect, what to do, and how to get through what can be an overwhelming, life-changing experience. This new edition includes tips for choosing the right doctor, understanding treatment choices, dealing with the effects of treatment, seeking support groups, and much more. A list of specific resources for patients, as well as a glossary of terms related to breast cancer, is also included"--